PENGARUH PEMBELAJARAN BERBASIS MASALAH DAN KECERDASAN NATURALIS TERHADAP KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH LINGKUNGAN HIDUP (Studi Eksperimen Di SMPN 1 Mataram NTB) - Suhirman Suhirman (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2012)
The objective of the research is to determine the influence of problem basedlearning, naturalistic intelligence, and their interaction on students’ ability inenvironment problem solving. The research was conducted at State Junior High School1 Mataram, Nusa Tenggara Barat, 2011 with n=36 selected randomly.The research are as follows: (1) the ability in environment problem solving ofthe students who learned using monolithic natural environment study is significanthigher than those who learned using integrated natural environment study (2) Theability in environment problem solving of those whose high naturalistic intelligence issignificant higher than those whose low naturalistic intelligence (3) the ability inenvironment problem solving for those whose high naturalistic intelligence but learnedusing monolithic natural environment study is significantly higher than those wholearned using the integrated one (4) the ability in environment problem solving forthose whose low naturalistic intelligence but learned using monolithic naturalenvironment study is not significant different from those who learned using theintegrated one (5) the ability in environment problem solving of those who learnedusing monolithic natural environment study but whose high naturalistic intelligence issignificant higher than those whose low naturalistic intelligence (6) the ability inenvironment problem solving of those whose low naturalistic intelligence but learnedusing monolithic natural environment study is not significant different from those wholearned using the integrated one.Based on the result of research, the students’ ability in solving environmentalproblems might be significantly improved by teaching them using monolithic approachas well as considering their naturalistic intelligence.